Exploring the nexus of education finance, governance, and sustainability in Somalia’s post-conflict education sector: a structural equation modeling analysis - Nor, Mohamed Ibrahim (Frontiers in Education, 2025)
This study examines the nexus between education finance, governance, and system sustainability in Somalia’s post-conflict education sector using structural equation modeling (SEM). The analysis identifies significant positive relationships between governance and education finance, finance and performance, and equitable access to education and system sustainability. The findings underscore the vital role of governance in managing financial resources to enhance educational outcomes and ensure long-term sustainability. The study offers actionable insights for policymakers and practitioners, highlighting the need to strengthen governance frameworks and financial management in post-conflict education systems. By employing SEM, the study provides a novel and comprehensive analysis of these complex relationships, contributing to the limited research on education finance and governance in post-conflict settings. This research offers empirical evidence from Somalia, adding new insights into the interplay between governance, finance, and education, and informing future policy and practice.